An Averaging Principle for Mckean–Vlasov-Type Caputo Fractional Stochastic Differential Equations - Weifeng Wang; Lei Yan; Junhao Hu; Zhongkai Guo (Journal of Mathematics)
In this paper, we want to establish an averaging principle for Mckean–Vlasov-type Caputo fractional stochastic differential equations with Brownian motion. Compared with the classic averaging condition for stochastic differential equation, we propose a new averaging condition and obtain the averaging convergence results for Mckean–Vlasov-type Caputo fractional stochastic differential equations.